Administrative Costs of Taxation in Slovakia - Juraj Nemec; Ladislav Pompura; Vladimír Šagát (European Financial and Accounting Journal, 2015)
This article reports an investigation into the administrative costs of the Slovak tax system. By applying methodology used in the Czech Republic, it analyses the administrative costs of taxation in Slovakia between 2004 and 2011. The results show that Slovakia has relatively high costs of tax administration compared to other developed countries, including its neighbours - the V4 countries. We argue that most of the higher relative cost is caused by subjective - speculative factors that will be addressed by ongoing tax system reforms.
Keywords: H20; 650; Administrative costs of taxation; Tax administration; Slovakia